Systematic literature review of methodologies and data sources of existing economic models across the full spectrum of Alzheimer’s disease and dementia from apparently healthy through disease progression to end of life care: a systematic review protocol - Karagiannidou, M; Wittenberg, R; Landeiro, F; Park, A; Fry, A; Knapp, M; Gray, A; Tockhorn-Heidenreich, A; Castro Sanchez, A; Ghinai, I; Handels, R; Lecomte, P; et al. (BMJ Publishing Group, 2018)
Introduction Dementia is one of the greatest health challenges the world will face in the coming decades, as it is one of the principal causes of disability and dependency among older people. Economic modelling is used widely across many health conditions to inform decisions on health and social care policy and practice. The aim of this literature review is to systematically identify, review and critically evaluate existing health economics models in dementia. We included the full spectrum of dementia, including Alzheimer’s disease (AD), from preclinical stages through to severe dementia and end of life. This review forms part of the Real world Outcomes across the Alzheimer’s Disease spectrum for better care: multimodal data Access Platform (ROADMAP) project. Methods and analysis Electronic searches were conducted in Medical Literature Analysis and Retrieval System Online, Excerpta Medica dataBASE, Economic Literature Database, NHS Economic Evaluation Database, Cochrane Central Register of Controlled Trials, Cost-Effectiveness Analysis Registry, Research Papers in Economics, Database of Abstracts of Reviews of Effectiveness, Science Citation Index, Turning Research Into Practice and Open Grey for studies published between January 2000 and the end of June 2017. Two reviewers will independently assess each study against predefined eligibility criteria. A third reviewer will resolve any disagreement. Data will be extracted using a predefined data extraction form following best practice. Study quality will be assessed using the Phillips checklist for decision analytic modelling. A narrative synthesis will be used. Ethics and dissemination The results will be made available in a scientific peer-reviewed journal paper, will be presented at relevant conferences and will also be made available through the ROADMAP project.